A non-linear harmonic analysis of potential induced fluorescence modulation of a DNA self assembled monolayer. (10th August 2017) - Yu, Zhinan L.; Leung, Kaylyn K.; Yu, Hua-Zhong; Bizzotto, Dan
Abstract: The characterization of a mixed mercaptohexanol - fluorophore labeled DNA self-assembled monolayer (SAM) on a single crystal gold bead electrode is demonstrated using an electrochemical perturbation and optical harmonic analysis scheme. This approach relies on the non-linear characteristics of the fluorescence intensity response towards a single frequency sinusoidal potential perturbation (163 Hz) which causes the DNA SAM to reorient, changing the efficiency of fluorescence quenching by the gold electrode. This results in a modulated fluorescence intensity that is composed of first, second and third harmonic signals which were found to strongly depend on the hybrization state of the DNA SAM, the DNA packing density on the surface, and the surface crystallography. Comparing the results between the different surface crystallographies on the same electrode and between different electrodes was simplified with a self-consistent normalization method reducing the influence of the raw fluorescence intensity. A significant difference in the second harmonic response was observed for single and double stranded DNA SAMs especially on the lower coverage (100) region and surfaces with related crystallographies. The third harmonic signal was weaker, but also showed a distinction between the hybridization states. Higher coverage (311) surface regions showed no significant fluorescence modulation nor any difference based on state of hybridization. Within a limited potential range, the electrochemical response (current) from the modified electrode did not show significant non-linearity revealing that the source of the harmonic signals was due to the non-linear relationship between the fluorescence quenching and fluorophore separation from the electrode surface. Increasing the amplitude of the potential perturbation increased the harmonic signal magnitudes further differentiating the DNA hybridization state.